Data Security Challenges with its Defence Strategies of Internet of Things: Critical Review Study - Al-Otaibi, Shuruq Zayed (Communications in Mathematics and Applications, 2022)
Due to the sensitivity of the data security issue and the lack of studies focused on data security in the Internet of Things (IoT) environment; this paper-through the methodology of critical review of relevant previous and recent studies-aimed to extract the most important challenges or problems and technical and defence strategies and solutions related to securing data in IoT. That is all In order to serve as a practical guide to benefit the concerned ones. As for the results of the studies, there were several things, including: that the most common security issues and challenges within the previous studies were: confidentiality, privacy and encryption effectiveness, and authentication methods are the best methods for securing data by nearly 60%, and the most important of these methods is lightweight authentication, multi-factor authentication, then mutual authentication. In addition, it is necessary to pay attention to securing all layers of the IoT. Especially the perception layer; as it is the main interface for the attack for easy physical access to the end nodes and web interfaces. Moreover, there are several modern technologies and methods that contribute to securing data such as: lightweight systems, digital twins, Software-Defined Network (SDN), edge computing and engineering, fog computing, trust computing, Context aware of accessibility. As for the recommendations, the study recommended all the following. IoT service providers should adopt several security methods, techniques and protocols in order to raise the level of security during data transfer and storage. The concerned organizations and bodies should issue unified laws and frameworks in order to standardize the work in IoT environment and In order to protect the confidentiality and privacy of data.
Keywords: Internet of Things; Data security; Confidentiality; Privacy; Authentication; Access control; IoT